Where we belong [compact disc, unabridged] : a novel - Giffin, Emily (Macmillan Audiobook, 2012)
Marian Caldwell has convinced everyone, including herself, that her life is just as she wants it to be. But one night, Marian answers a knock on the door, only to find Kirby Rose, an eighteen-year-old girl with a key to a past that Marian thought she had sealed off forever. As the two women embark on a journey to find the one thing missing in their lives, each will come to recognize that where we belong is often where we least expect to find ourselves.